Просторова самоорганізація населення: теоретико-методологічні передумови дослідження - Прибиткова, І. (Социология: теория, методы, маркетинг, 2009)
There are discussed the phenomenon of a space self-organization of population and theoretical and methodological premises of its investigation. The author proceeds from assumption that the forming of space preferences reflects the reactions of individuals on certain totality of characteristics of their surroundings stipulated by economical, social and psychological reasons. The selective attitudes of people towards places of their inhabitancy can serve as a criterion for quality of life at any place within the space of potentialities. They can be regarded also as an identification signs of latent groups of population with their specific social organization, behavior, claims and purposes. The most wide-spread models used in researches of space interactions are analyzed in the article. The author, on her part, adheres to opinion that the study of spatial relations should be based on the mapping to provide the most complete description and comprehension of territorial differences between patterns of human activity. There presented the cartographical models of space self-organization of rural po pulation in Ukraine. The comparison of identical models for a few years in succession gives us the notion about the nature and rate of changes and development of spatial structures and discovers the important spatial relations between movements of rural inhabitants and urbanization in Ukraine.